Berechnung von mittleren Schwingungsamplituden nach der Methode der charakteristischen Schwingungen von Müller - Baran, Enrique José (1970)
It is shown for many molecules and ions that the "Methode der charakteristischen Schwingungen" of Müller is usefull for the calculation of mean amplitudes of vibrations if the vibrations are rather characteristic.